2019
DOI: 10.3390/antibiotics8020074
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Lytic Bacteriophage as an Antimicrobial Agent for Biocontrol of Shiga Toxin-Producing Escherichia coli O145 Strains

Abstract: Shiga toxin-producing Escherichia coli (STEC) O145 is one of the most prevalent non-O157 serogroups associated with foodborne outbreaks. Lytic phages are a potential alternative to antibiotics in combatting bacterial pathogens. In this study, we characterized a Siphoviridae phage lytic against STEC O145 strains as a novel antimicrobial agent. Escherichia phage vB_EcoS-Ro145clw (Ro145clw) was isolated and purified prior to physiological and genomic characterization. Then, in vitro antimicrobial activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Ibrahim (1969) reported that E. coli phages were also effective against some Salmonella serovars. Liao et al (2019) (Necel et al, 2020). Chang and Kim (2011) Results from the present study are similar to these studies, revealing that some isolated phages are infective against E. coli O157:H7 strains with high target specificity and some isolated phages are infective against other E. coli strains and some Salmonella enterica serovars in addition to E. coli O157:H7 strains.…”
Section: Resultssupporting
confidence: 86%
“…Ibrahim (1969) reported that E. coli phages were also effective against some Salmonella serovars. Liao et al (2019) (Necel et al, 2020). Chang and Kim (2011) Results from the present study are similar to these studies, revealing that some isolated phages are infective against E. coli O157:H7 strains with high target specificity and some isolated phages are infective against other E. coli strains and some Salmonella enterica serovars in addition to E. coli O157:H7 strains.…”
Section: Resultssupporting
confidence: 86%
“…During the incubation, 1 mL of sample was collected at a 2 min interval for phage Ro103C3lw (for a total of 20 min) and a 5 min interval for phage Pr103Blw (for a total of 55 min). The sample from each time point was flited through a sterile 0.22-μm membrane filter for double-layer plaque assay to determine phage latent periods using the similar protocol, as described previously [ 35 ]. The plates were incubated at 37 °C for 24 h. The one-step growth curve experiment of each phage was performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…Two research groups isolated phages phiC119 and AKFV33, both targeted specifically against STEC O157 strains, were evaluated their biocontrol potential, including host range and lysis time, and identified the presence of harmful genes [ 33 , 34 ]. We previously isolated and characterized a lytic bacteriophage vB_EcoS-Ro145clw with antimicrobial activity against STEC O145 and E. coli O145:H28 outbreak strains [ 35 ]. We also investigated genomic characteristics of the phage contributing to phage stability and antimicrobial activity for a broad phage application in various environments.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, the principal efforts of using bacteriophages against STEC strains have been directed mainly toward serogroup O157 (O'Flynn et al, 2004;Abuladze et al, 2008;Sharma et al, 2009;Viazis et al, 2011;Hudson et al, 2015;Snyder et al, 2016). However, given the increase in the finding of non-O157 in food, different authors have focused their efforts also toward other serogroups (Tomat et al, 2013;Tolen et al, 2018;Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%